Research on the Estimation Method of the Stiffness Degeneration Index of Reinforced Concrete Members - Yukui Wang; Zhefeng Liu; Weijun Yang; Jian Wang; Xiao Zheng (Advances in Civil Engineering)
Based on variable amplitude displacement cycle tests of 24 reinforced concrete members with different reinforcement conditions, the stiffness degradation index was proposed to describe the damage. The relationship between the stiffness degradation index, the displacement history, and the cumulative energy dissipation was studied; on this basis, an estimation method for the stiffness degradation index was proposed. By comparing the experimental values and estimated values of the stiffness degradation index, the proposed method provides promising prediction reliability and accuracy. The stiffness degradation index has an effective relationship with the structural design parameters. Based on the stiffness degradation index, the reinforced concrete members can be divided into five performance levels: no damage (DK,k < 0), mild damage (0 < DK,k ≤ 0.3), moderate damage (0.3 < DK,k ≤ 0.7), severe damage (0.7 < DK,k ≤ 0.9), and destruction (0.9 < DK,k ≤ 1), which can provide a good reference for the seismic design of reinforced concrete members. The increase in the transverse reinforcement ratio can significantly reduce the stiffness damage, and the effect is more obvious under the conditions of small ductility. Under the same conditions, the smaller the ductility condition is, the smaller the stiffness damage of the reinforced concrete members will be. Therefore, the control of the ductility condition and the increase in the transverse reinforcement ratio are stable and effective methods for controlling the stiffness damage of reinforced concrete members.